The experimental foundations of particle physics - Cahn, Robert N. (Cambridge University Press, 2009)
Our current understanding of elementary particles and their interactions emerged from break-through experiments. This book presents these experiments, beginning with the discoveries of the neutron and positron, and following them through mesons, strange particles, antiparticles, and quarks and gluons. This second edition contains new chapters on the W and Z bosons, the top quark, B-meson mixing and CP violation, and neutrino oscillations. This book provides an insight into particle physics for researchers, advanced undergraduate and graduate students. Throughout the book, the fundamental equations required to understand the experiments are derived clearly and simply. Each chapter is accompanied by reprinted articles and a collection of problems with a broad range of difficulty.